Consumer-driven innovation in food and personal care products - Jaeger, Sara R.; MacFie, H. J. H. (Woodhead Pub., 2010)
Experts from around the world present changes in the global marketplace and developments in research methodologies underpinning new product development (NPD) in this essential collection. The business and marketing aspects of NPD, sometimes neglected in books of this type, are addressed alongside methods for product testing. Trends, processes and perspectives in consumer-driven NPD in the food and personal care product industries are addressed in the opening chapters of the book. Specific topics include evolution in food retailing and advances in concept research. Hedonic testing is the focus of the next section. Different viewpoints on consumer research methods and statistics for NPD are reviewed in later chapters. The final part of the book looks towards the future of innovation, covering the implications for NPD of topics such as human genetic variation in taste perception and neuroimaging. Several chapters are not standard scientific articles. Rather they are written records of conversations between two people on a particular topic related to consumer-driven innovation in foods and personal care products. In them the interviewees speak freely about their views and experiences in NPD, providing unique insights. Consumer-driven innovation in food and personal care products will broaden readers' understanding of the many approaches available to NPD personnel and ways in which they can be used to support innovation activities. Provides expert insight into the changes in the global market place and developments in research methodologies underpinning NPDExamines the business and marketing aspects of NPD, sometimes neglected in books of this type, are addressed alongside methods for product testingChapters review the different viewpoints on consumer research methods and statistics for NPD.
"Plant & Food Research, Rangahau Ahumara Kai."
Keywords: Food industry and trade -- Technological innovations.; Cosmetics -- Technological innovations.; elektronické knihy; electronic books